Filling model of oil and polar liquid for electrowetting displays based on phase change - Jiang, Hongwei; Qian, Rongzhen; Chen, Wenwen; Zhou, Rui; Zhou, Guofu (Frontiers in Physics, 2022)
Reflective displays have recently attracted more and more attention because of the advantages of low power consumption and eye protection. Among them, electrowetting display (EWD) has become the most potential reflective display technology due to its full color and video speed advantages. However, filling models of oil and polar liquids in electrowetting displays were rarely reported, which could not solve the low efficiency and filling defects so far for EWDs. In this paper, a novel filling model based on oil phase change (Phase change filling) was proposed, and related equipment was designed and fabricated. Compared with traditional filling ways, the efficiency of the phase change filling was greatly improved. Since the process of dosing oil into a pixel was released into air environment, the dosing method was significantly enriched, and dosing accuracy was more controllable. The experimental results showed that we obtained a good response time and a high pixel aperture ratio, which were 31.78 ms and 68.2%, respectively.